Inca Huamachuco: Warrior Dance Ritual - Escamilo Cardenas, Simon (2015)
This paper is about a originated in the early sixteenth century dance, having as its central theme the death of the Inca Atahualpa in Cajamarca City. Every year between 14 and 15 August, the feast day is celebrated in honor of the Virgin of Alta Gracia. In this dance festival presents the Incas, led by an enigmatic character called Cusco, charged with enforcing order and discipline; plus dance consists of several characters (Inca King, King Nusta and Others) in which each author (Peasants Hamlet Stone Bridge, District of Huamachuco) represents, reconstructs what happened in Cajamarca. The staging, choreography, clothing also chants and their contents; greetings and bows to the senior officials; the location of each character according to their social position in the dance; gestures and dancing with martial and warrior musical background, do their analysis and understanding very suggestive.